Psychological needs support training for coaches: An avenue for nurturing mental toughness - Mahoney, J.; Gucciardi, D.; Gordon, S.; Ntoumanis, Nikos (2016)
Sport regularly provides examples of exceptional feats against the odds; unprecedented exhibitions of skill and mastery; impressive streaks of success; and stories of fortitude, persistence, and tenacity. Undoubtedly, there are a considerable number of factors – some of which are difficult to identify, let alone repeat – that contribute to these occurrences. For over a decade, sport psychology researchers have typically considered the psychological factors believed central to athletic performances under one banner, namely mental toughness. In this chapter, we present a brief description of mental toughness, as well as outline a coach entered intervention designed to develop mental toughness in athletes. We also outline and detail the underlying framework for our intervention (i.e., self-determination theory) and illustrate the processes of implementing such an intervention by drawing on a case study example.